Uncovering Common Errors in Gerunds and Infinitives among EFL Students - Haris Hamdani; Venti Mawarni; Nurhasanah Nurhasanah (Jurnal Inovasi dan Riset Pendidikan Dasar, 2026)
This study aimed to uncover common errors in the use of gerunds and infinitives among EFL students in sentence construction and paragraph writing. This study involved 40 EFL undergraduate students and employed a qualitative descriptive design using writing tasks and semi-structured interviews as the primary instruments for data collection. The findings revealed that students frequently made errors related to the misuse of gerunds and infinitives. The most dominant error was the incorrect use of infinitives after verbs that require gerunds, followed by the use of “to + verb-ing” structures and inappropriate use of base verbs in contexts requiring specific verb complementation patterns These recurring errors indicated that students tended to overgeneralize grammar rules and relied on simplified sentence structures when they were uncertain about the correct forms. The interview results further showed that students experienced confusion because different verbs require different grammatical patterns, while some verbs can be followed by both gerunds and infinitives with changes in meaning. Students also reported difficulties in creating varied and natural sentence structures while maintaining grammatical accuracy. To overcome these problems, most participants relied on memorization strategies, grammar notes, online examples, and peer discussions. However, these strategies were not always effective in developing deeper grammatical understanding and automatic language use. The study concluded that the complexity of English verb complementation patterns, limited contextualized grammar practice, and insufficient communicative writing activities contributed significantly to students’ grammatical difficulties. Therefore, the study recommends that English lecturers provide more interactive and contextualized grammar instruction through varied exercises, collaborative activities, and detailed corrective feedback. In addition, students should increase their exposure to authentic English materials to strengthen their understanding and practical use of gerunds and infinitives in writing activities. Theoretically, this study contributes to the growing body of research on English grammatical acquisition by providing empirical evidence that learners’ errors are strongly influenced by rule overgeneralization and incomplete mastery of verb complementation patterns. The findings also extend Error Analysis research by integrating qualitative insights from student interviews, offering a more comprehensive understanding of the cognitive and instructional factors underlying learners’ difficulties with gerunds and infinitives.